Analyzing Digital Maturity as an Implementation to Assess the Responsiveness of E-Government - Wiranto, Dwi; Nurmandi, Achmad; Lawelai, Herman; Younus, Muhammad; Suardi, Wahdania (Journal The Winners, 2025)
The research analyzed digital maturity in assessing the responsiveness of e-government services. The research is driven by the issue that many governments struggle to deliver responsive and efficient digital services due to uneven levels of digital maturity. Technological infrastructure gaps, limited digital competencies, and rigid bureaucratic processes hinder the creation of adaptive e-government systems. Using a scientometric analysis method, the research evaluated literature published from 2019 to 2024, sourced from the Scopus database, and employed RStudio and CiteSpace tools for data visualization and trend mapping. The findings reveal that high levels of digital maturity significantly improved public service efficiency, transparency, and citizen engagement. These improvements are achieved through effective integration of digital technology, organizational transformation, and citizen-centered service design. The research also identifies persistent challenges, such as low digital literacy, infrastructure inequality, resistance to change, and data security concerns, all of which obstruct the realization of responsive e-government. The research contributed originality through a multidimensional approach, offering a strategic framework to evaluate e-government effectiveness using digital maturity indicators such as accessibility, service quality, and public satisfaction. It emphasizes the need for sustained investment in infrastructure, digital literacy programs, and cross-sector collaboration involving the government, private sector, and civil society. Additionally, it identifies opportunities for future research to explore how emerging technologies—such as artificial intelligence, blockchain, and big data—can enhance transparency, efficiency, and inclusivity in public services. Overall, the research positions digital maturity as a key enabler of adaptive and effective governance in the digital era.